Implementasi Model Pembelajaran Teaching at The Right Level (TaRL) dalam Meningkatkan Kemampuan Literasi - Hasanah, Uswatun; Junaidi, Eka; Supriadi, Supriadi; Ahmad, Ahmad (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
The action in this study aims to improve students' reading literacy skills at SDN 46 Ampenan using a learning model (Teaching at the Right Level). This research is a Classroom Action Research (PTK) conducted in February 2024 with the object of fourth grade students of SDN Ampenan. Data collection techniques are tests, observation and documentation. The result is that the achievement of students' literacy skills has increased statistically in the count of cycles after applying the TaRL learning model. The results of the average ability of pre-cycle students in the sufficient category 77.96 (67%). Then in Cycle I there was an increase but not significant with a good category of 80.21 (83%). However, in cycle II, the percentage of students' average scores increased significantly with a very good category of 90.83 (95%). the TaRL learning concept emphasises the characteristics of students so that students are treated according to their needs. The TaRL learning model provides a positive effect and becomes an alternative solution in overcoming students' reading literacy problems.